Internationalization of Higher Education in Costa Rica The experience of a dual Master's degree at Universidad Nacional - Pichardo Muñiz, Arlette (2016)
Costa Rica has promoted international student and academic mobility for several decades, going as far as hosting international higher education programs. The International Center on Economic Policy for Sustainable Development (CINPE, for its acronym in Spanish) at Universidad Nacional (UNA, for its acronym in Spanish) has joined the Technology Institute of Santo Domingo (INTEC, for its acronym in Spanish), Dominican Republic, to teach the Master’s Degree in International Trade Management. This is the first program of its kind known to date in the country and probably in Central America, in which a Costa Rican university provides the curriculum and takes a leading academic position, with transculturality becoming an added value. This paper is aimed at sharing the lessons learned in this experience that may be useful in similar initiatives. In general, the results of the systematization suggest the following: (1) including international and intercultural perspectives implies internationalizing locally; (2) creating initial conditions to advance in the internationalization process does not happen overnight; (3) management implies innovative solutions agreed by all; and (4) due attention should be paid to the harmonization of procedures, instruments, and forms. Some conclusions are drawn based on the main findings, particularly regarding the implications of a program of this nature or others with similar characteristics.